A Fast Interactive Sequential Pattern Mining Algorithm - Lu, Jie-Ping; Liu, Yue-Bo; Ni, Wei-Wie; Liu, Tong-Ming; Sun, Zhi-Hui (Wuhan University journal of natural sciences, 2006)
In order to reduce the computational and spatial complexity in rerunning algorithm of sequential patterns query, this paper proposes sequential patterns based and projection database based algorithm for fast interactive sequential patterns mining algorithm （FISP）, in which the number of frequent items of the projection databases constructed by the correct mining which based on the previously mined sequences has been reduced. Furthermore, the algorithm＇s iterative running times are reduced greatly by using global-threshold. The results of experiments testify that FISP outperforms PrefixSpan in interactive mining